2019
DOI: 10.1681/asn.2018060599
|View full text |Cite
|
Sign up to set email alerts
|

LRG1 Promotes Diabetic Kidney Disease Progression by Enhancing TGF-β–Induced Angiogenesis

Abstract: Background Glomerular endothelial dysfunction and neoangiogenesis have long been implicated in the pathogenesis of diabetic kidney disease (DKD). However, the specific molecular pathways contributing to these processes in the early stages of DKD are not well understood. Our recent transcriptomic profiling of glomerular endothelial cells identified a number of proangiogenic genes that were upregulated in diabetic mice, including leucine-rich a-2-glycoprotein 1 (LRG1). LRG1 was previously shown to promote neovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(127 citation statements)
references
References 67 publications
13
97
0
Order By: Relevance
“…A previous study showed that LRG1 promoted angiogenesis by modulating endothelial TGF-β signaling [5]. We also found that LRG1 promoted diabetic kidney disease progression by enhancing TGF-β-induced angiogenesis [6]. TCGA analysis showed that TGF-β expression was upregulated in ccRCC patients ( Figure 5(a)).…”
Section: Lrg1 May Promote Ccrcc Progression Via the Tgf-supporting
confidence: 51%
See 2 more Smart Citations
“…A previous study showed that LRG1 promoted angiogenesis by modulating endothelial TGF-β signaling [5]. We also found that LRG1 promoted diabetic kidney disease progression by enhancing TGF-β-induced angiogenesis [6]. TCGA analysis showed that TGF-β expression was upregulated in ccRCC patients ( Figure 5(a)).…”
Section: Lrg1 May Promote Ccrcc Progression Via the Tgf-supporting
confidence: 51%
“…LRG1 has a close relationship with TGF-β. Our previous work demonstrated that LRG1 significantly accelerated diabetic kidney injury and TGF-β/ALK1-induced angiogenesis in an experimental model of early diabetic kidney disease [6]. Consistently, LRG1 promotes angiogenesis by modulating endothelial TGF-β signaling in retinal vascular [5] and NSCLC [22].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, it was largely preserved by treatment with AMD3100 (Figure F, J, and K). To further confirm the role of CXCR4 in tubular cell injury, we examined the mRNA expression of neutrophil gelatinase–associated lipocalin (NGAL) and transforming growth factor‐β1 (TGF‐β1), two markers of tubular cell injury by quantitative real‐time PCR. As shown in Figure L and M, administration of AMD3100 significantly blocked UUO‐induced up‐regulation of NGAL and TGF‐β1.…”
Section: Resultsmentioning
confidence: 99%
“…We recently observed that leucine-rich a-2-glycoprotein 1 (Lrg1) was upregulated in GECs in the same diabetic mouse model using bulk RNA-seq, 4 and we further demonstrated that it plays an important role in early diabetic endothelial injury (Hong et al, this issue). 31 Interestingly, its expression in single cells showed that the observed increase in bulk endothelial cells may be in large part due to a greater number of individual endothelial cells expressing Lrg1 in the diabetic conditions ( Figure 6). Because variability in gene expression detected in single-cells may also be due to background (technical) noise, further studies are required to confirm the variability of Lrg1 expression in individual cells as a contributor to its increased expression in the diabetic kidneys.…”
Section: Scrna-seq Reveals Dynamic Changes In Gene Expression In Endomentioning
confidence: 98%